Consistent high prevalence of undiagnosed blood‐borne virus infection in patients attending large urban emergency departments in England - Hopkins, Mark J. (J Viral Hepat, 2019)
Understanding local viral hepatitis and HIV epidemiology is essential if WHO elimination targets are to be achieved. We demonstrate a consistently high prevalence of undiagnosed active infection in urban emergency department attendees in England, with variations in local risk groups crucial to informing targeted testing initiatives.